Implementasi Teams Games Tournaments dan Number Head Together ditinjau dari Kemampuan Penalaran Matematis - Rahmawati, Nurina Kurniasari (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
The purpose of this study was to determine the effect of Teams Games Tournaments (TGT) and Numbered Head Together (NHT) learning models on mathematics achievement that reviewed students' mathematical reasoning abilities. The research method applied is experimental research. The type of research used is quasi experiment research. The research design used a 3 × 3 factorial design. The research sample was taken using cluster random sampling technique. Data collection used is using two types, namely documentation and tests. The instrument used for data collection consists of tests of mathematical reasoning abilities and tests measuring the ability of students' learning achievement. The test of mathematical reasoning ability is in the form of multiple choice test questions, while learning achievement tests are in the form of objective test questions that contain the sequence and series material according to the indicators measured. Hypothesis testing used is a parametric test with data analysis techniques using the Anova test. The results of the prerequisite test were carried out based on the normality test which can be known by using the Liliefors test and the homogeneity test can be known by using the Barlett test. two paths with cells are not the same. The results of this research review, namely there is the effect of TGT and NHT learning models on students' mathematical reasoning abilities; Mathematical achievement with the TGT model is better than mathematics achievement with NHT learning models and Conventional learning; and students with high mathematical reasoning abilities have better learning achievement compared to moderate and low mathematical reasoning abilities.